Internal Auditing and Sustainability of Small and Medium Enterprises in Uganda (Vallis Aurea, 2024)
This study investigates the relationship between internal auditing and sustainability of small and medium enterprises in Uganda using institutional theory. This research was cross-sectional based on data collected from 361 enterprises. Data were analyzed using the Statistical Package for Social Sciences and Structural Equation Modelling. The results reveal a significant positive relationship between internal auditing (in terms of controls, procedures and practices) and sustainability of small and medium enterprises. Based on the findings, managers should adhere to strictly designed work procedures that possess minimum chances of incurring financial losses to ensure businesses survival in the current competitive business environment.